Socioeconomic development and human well-being: BRAC-ICDDR,B joint research project, Matlab (phase II) - Husain, Shahed; Husain, Gazi Mahmud; Ahmed, Syed Masud; Chowdhury, Mushtaque; Bhuiya, Abbas; Khan, Monirul Islam (BRAC, 2019)
This report documents the first round of the seasonal survey with respect to household economy covering land holdings, savings and loans, employment and expenditure. For collecting household information, the household heads were interviewed. In most cases, the heads were male members. In the absence of male household head, other responsible member who can provide reliable information about the household was interviewed. In the study area, a preponderance of female headed HHs (19.30%) was observed compared to the national figure of 7 .63%. Female headship was most prevalent among TO non-member. Literacy rate of HH heads was highest among NTO HHs followed by BRAC member HHs and TO nonmember HHs, and these differences are significant. Agriculture and labor selling were the most common occupation for the HH heads. NTO HHs were more likely to be involved in agriculture, while BRAC member HHs and TO non-member HHs were most likely to be engaged in labour selling. Contribution to HH's income was most likely in case of BRAC members who were also HH's head as well.NTO HHs possessed the largest amount of land followed by BRAC member HHs and TO nonmember HHs. BRAC member HHs possessed almost twice as much land as TO non-member HHs. The percentage of landless is the highest among TG non-member HHs followed by BRAC member HHs and NTO HHs. BRAC member HHs possess twice the amount of cultivable land compared to TG non-member HHs. NTO HHs have the highest value of total non-land assets followed by BRAC member HHs and TO non-member HHs. NTO HHs have the highest amount of mean total savings followed by BRAC member HHs and TO non-member HHs. BRAC member HHs possess nearly twice as much savings as TO nonmember HHs . Most of the savings take place under the heading of crop savings for all HHs. NTO HHs borrowed the highest amount followed by BRAC member HHs and TO non-member HHs. BRAC member HHs borrowed mostly from BRAC, where TG non-member HHs and NTG HHs borrowed mostly from relatives. Second most common source of loan was money lender for BRAC member HHs and TO non-member HHs, but mortgages for NTG HHs. It was observed that BRAC member HHs utilized the highest percentage of the loan for income generation followed by NTO HHs and TO non- member HHs. Type of employment is divided into two categories: self employment and wage employment. Self and wage employment are further disaggregated by gender. Men from all HHs spent more time in self employment than in wage employment. Overall, men spent 43 .6 hours in employment whereas women spent only 6.3 hours or only 14.4% of the time spent by men in employment for previous seven days in the srudy area. Men from NTO HHs spent greater time in self employment whereas BRAC member HHs spent greater time in wage employment. The two major components of total expenditure are food items and non-food items. NTO HHs expenditure on both food and non-food was the highest followed by BRAC member HHs and TO non-member HHs. The differences among BRAC member HHs, TO non-member HHs and NTG HHs on food expenditure were less compared to non-food expenditures. NTO HH's income from cultivation was thrice as much as BRAC member HHs and BRAC member HHs earned nearly double compared to TG non-member HHs.